Prenatal ultrasound and magnetic resonance evaluation and fetal outcome in high‐risk fetal tumors: A retrospective single‐center cohort study over 20 years. (26th June 2020) - Ulm, Barbara; Muin, Dana; Scharrer, Anke; Prayer, Daniela; Dovjak, Gregor; Kasprian, Gregor
Abstract: Introduction: Fetal tumors are rare and usually followed by poor outcome. We describe our single‐center experience with fetal tumors evaluated by ultrasound and magnetic resonance imaging (MRI). Our aims were to evaluate mortality and morbidity including long‐term outcome and to determine which ultrasound and MRI characteristics were helpful for pre‐ and perinatal management. Material and methods: We conducted a retrospective analysis on prenatally diagnosed tumors between 1998 and 2018. Poor outcome included fetal or neonatal death and survival with serious illness. MRI addressed tumor morphology (sacrococcygeal teratomas), compromise of surrounding structures (head and neck tumors) and early depiction of brain alterations specific to tuberous sclerosis (rhabdomyomas). Results: Of 68 pregnancies, 15 (22%) were terminated and eight children (8/53, 15%) died pre‐ or postnatally. Of the 45 survivors (45/68, 66%), 24 (24/45, 53%) were healthy, eight (8/45, 18%) had a minor illness and 13 (13/45, 29%) a serious illness. Diffusion‐ and T1‐weighted MRI reliably predicted tumor morphology in teratomas. To detect head and neck tumors critical to airway obstruction, MRI was superior to ultrasound in delivery planning. Rhabdomyomas were frequently associated with tuberous sclerosis, regardless of their number or size in ultrasound; MRI could depict specific brain alterations from the early third trimester onwards. For several rare tumors, MRI provided critical differential diagnoses that could not be clearly displayed in ultrasound. Conclusions: The rate of survivors with serious long‐term illness among fetuses with prenatal diagnosis of a tumor was high. MRI is specifically helpful for risk stratification in fetal teratomas and delivery planning in head and neck tumors.